Case of bovine fetal mummification and secondary maceration with fetal bones embedded in myometrium - DADARWAL, DINESH; MISHRA, YOGI; GANDOTRA, V K (The Indian Journal of Animal Reproduction, 2023)
Case if fetal mummification and secondary maceration has been studied in this paper.
Keywords: Bovine; fetal mummification; myometrium